De Novo SOX4 Variants Cause a Neurodevelopmental Disease Associated with Mild Dysmorphism. - Zawerton, Ash; Yao, Baojin; Yeager, J Paige; Pippucci, Tommaso; Haseeb, Abdul; Smith, Joshua D; Wischmann, Lisa; Kühl, Susanne J; Dean, John C S; Pilz, Daniela T; Holder, Susan E; McNeill, Alisdair; et al. (Am J Hum Genet, 2019)
SOX4, together with SOX11 and SOX12, forms group C of SRY-related (SOX) transcription factors. They play key roles, often in redundancy, in multiple developmental pathways, including neurogenesis and skeletogenesis. De novo SOX11 heterozygous mutations have been shown to cause intellectual disability, growth deficiency, and dysmorphic features compatible with mild Coffin-Siris syndrome. Using trio-based exome sequencing, we here identify de novo SOX4 heterozygous missense variants in four children who share developmental delay, intellectual disability, and mild facial and digital morphological abnormalities. SOX4 is highly expressed in areas of active neurogenesis in human fetuses, and sox4 knockdown in Xenopus embryos diminishes brain and whole-body size. The SOX4 variants cluster in the highly conserved, SOX family-specific HMG domain, but each alters a different residue. In silico tools predict that each variant affects a distinct structural feature of this DNA-binding domain, and functional assays demonstrate that these SOX4 proteins carrying these variants are unable to bind DNA in vitro and transactivate SOX reporter genes in cultured cells. These variants are not found in the gnomAD database of individuals with presumably normal development, but 12 other SOX4 HMG-domain missense variants are recorded and all demonstrate partial to full activity in the reporter assay. Taken together, these findings point to specific SOX4 HMG-domain missense variants as the cause of a characteristic human neurodevelopmental disorder associated with mild facial and digital dysmorphism.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Animals; Child; Child, Preschool; Coffin-Lowry Syndrome; Cohort Studies; Conserved Sequence; DNA; Female; Heterozygote; HMG-Box Domains; Humans; Male; Mutation, Missense; Neurodevelopmental Disorders; SOXC Transcription Factors; Transcriptional Activation; Xenopus

Congenital nephrotic syndrome in an infant with ALG1-congenital disorder of glycosylation. - Harshman, Lyndsay A; Ng, Bobby G; Freeze, Hudson H; Trapane, Pamela; Dolezal, Anna; Brophy, Patrick D; Brumbaugh, Jane E (Pediatr Int, 2016)
Congenital nephrotic syndrome (NS) in the newborn is most frequently related to mutations in genes specific for structural integrity of the glomerular basement membrane and associated filtration structures within the kidney, resulting in massive leakage of plasma proteins into the urine. Occurrence of congenital NS in a multi-system syndrome is less common. We describe the case of an infant with deteriorating neurological status, seizures, edema, and proteinuria who was found to have a mutation in gene ALG1 and a renal biopsy consistent with congenital NS. Furthermore, we briefly review rare existing case reports documenting congenital NS in patients with mutations in ALG1, and treatment strategies, including novel use of peritoneal dialysis.
Keywords: Abnormalities, Multiple; Congenital Disorders of Glycosylation; DNA; DNA Mutational Analysis; Glycosylation; Humans; Infant, Newborn; Male; Mannosyltransferases; Mutation; Nephrotic Syndrome; Peritoneal Dialysis

Laterality defects other than situs inversus totalis in primary ciliary dyskinesia: insights into situs ambiguus and heterotaxy. - Shapiro, Adam J; Davis, Stephanie D; Ferkol, Thomas; Dell, Sharon D; Rosenfeld, Margaret; Olivier, Kenneth N; Sagel, Scott D; Milla, Carlos; Zariwala, Maimoona A; Wolf, Whitney; Carson, Johnny L; Hazucha, Milan J; et al. (Chest, 2014)
BACKGROUND: Motile cilia dysfunction causes primary ciliary dyskinesia (PCD), situs inversus totalis (SI), and a spectrum of laterality defects, yet the prevalence of laterality defects other than SI in PCD has not been prospectively studied. METHODS: In this prospective study, participants with suspected PCD were referred to our multisite consortium. We measured nasal nitric oxide (nNO) level, examined cilia with electron microscopy, and analyzed PCD-causing gene mutations. Situs was classified as (1) situs solitus (SS), (2) SI, or (3) situs ambiguus (SA), including heterotaxy. Participants with hallmark electron microscopic defects, biallelic gene mutations, or both were considered to have classic PCD. RESULTS: Of 767 participants (median age, 8.1 years, range, 0.1-58 years), classic PCD was defined in 305, including 143 (46.9%), 125 (41.0%), and 37 (12.1%) with SS, SI, and SA, respectively. A spectrum of laterality defects was identified with classic PCD, including 2.6% and 2.3% with SA plus complex or simple cardiac defects, respectively; 4.6% with SA but no cardiac defect; and 2.6% with an isolated possible laterality defect. Participants with SA and classic PCD had a higher prevalence of PCD-associated respiratory symptoms vs SA control participants (year-round wet cough, P < .001; year-round nasal congestion, P = .015; neonatal respiratory distress, P = .009; digital clubbing, P = .021) and lower nNO levels (median, 12 nL/min vs 252 nL/min; P < .001). CONCLUSIONS: At least 12.1% of patients with classic PCD have SA and laterality defects ranging from classic heterotaxy to subtle laterality defects. Specific clinical features of PCD and low nNO levels help to identify PCD in patients with laterality defects. TRIAL REGISTRY: ClinicalTrials.gov; No.: NCT00323167; URL: www.clinicaltrials.gov.
Keywords: Adolescent; Adult; Biopsy; Child; Child, Preschool; Cilia; DNA; DNA Mutational Analysis; Female; Humans; Infant; Infant, Newborn; Kartagener Syndrome; Male; Microscopy, Electron, Transmission; Middle Aged; Mutation; Prevalence; Prospective Studies; Tomography, X-Ray Computed; United States; Young Adult